A Climate Change Board Game for Interdisciplinary Communication and Education. (April 2013) - Eisenack, Klaus
This article reports and reflects on the design and use of the board game KEEP COOL on climate change. The game covers and integrates central biophysical, economic, and political aspects of the issue. By using a board game as common language between students and scientists from different scientific cultures, knowledge of different disciplines can be integrated and different views can be discussed. Thus, even complex issues such as the free-rider problem, trade-offs between adaptation to and mitigation of climate change, and path dependencies can be studied. KEEP COOL is the first game on climate change that is readily available from a commercial publisher. It has successfully been used in multiple settings, for example, as a tool for interdisciplinary research, public relations, public understanding of science, and, in particular, teaching. The experience with the game indicates that it can be effectively used in seminars with students to obtain a holistic picture of the issue and to lay out a common language for deeper reflections on climate change. This contribution also identifies some pitfalls and essential instruments for its adequate use for teaching.